Tainted by Deception: Reading Virgil’s Dido in Light of Ovid’s Dido - Wesołowska, Elżbieta (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The paper aims to reveal some aspects of deception and falsity in Virgil and Ovid’s famous portrayals of an unhappy Dido. Paradoxically, such a view helps us to understand not only the sophisticated game between the younger and older poet, but also the special tension existing in the structure of the image of Dido, Queen of Carthage, deceived or only abandoned by the Roman hero Aeneas.